Pengaruh Pemberian Propolis Dan Honey Terhadap Penyembuhan Luka Ulkus Diabetes Mellitus Di Praktik Mandiri Alfa Care Center Kota Bengkulu Tahun 2024 - Zantika, Ninalia; Darmawansyah, Darmawansyah; Susanti, Meri Epriana (Jurnal Kesehatan Mitra Sekawan, 2025)
Indonesia is the fifth largest diabetic in the world with 19.5 million people with Diabetes Mellitus (DM) aged 20-79 years. The purpose of this study was conducted to determine the effect of giving Propolis and Honey on the healing of Diabetes Mellitus Ulcers in Alfacare Center Independent Practice, Bengkulu City in 2024. Method This research is quantitative using a quasy experimental design with a Pre-post test one group research design bivariate statistical test T-Test test with BJWAT wound status continuum measuring instrument Research technique total sampling with a total sample size of 15 respondents at Alfacare Center Independent Practice Bengkulu City. The results of the univariate test analysis of the Bates Jensen score assessment before being given action, out of 15 respondents there were 8 (53%) most of the respondents with moderate wound severity. assessment of the Bates Jensen score after being given action there were 8 (53.3%) most of the respondents experienced healing into the minimal wound severity category. The results of bivariate analysis p-value = 0.001 <0.05 Ho is rejected there is an effect of giving Propolis and Honey on wound healing of diabetes mellitus ulcers at Alfacare Center Independent Practice Bengkulu City in 2024. Suggestions Researchers suggest that the Alfacare Center can provide socialization to patients about care, ulcer wound factors, the benefits of Propolis and Honey on healing diabetes mellitus ulcers.